An unexpected synergistic toxicity caused by competitive bioconcentration of perfluoroalkyl acid mixtures to Daphnia magna: Further promoted by elevated temperature. (15th December 2022) - Zhang, Qianru; Zhang, Yidi; Hu, Diexuan; Wen, Wu; Xia, Xinghui
Abstract: The mixed pollution of the global water environment by perfluoroalkyl acids (PFAAs) and their ecological risks have aroused widespread concern. However, the relationship between the combined toxicity of PFAA mixtures and their accumulation in aquatic organisms is not well understood in the context of global warming. Here, we study the bioconcentration and combined toxicity of three PFAA mixtures (PFOA, PFDA, PFDoA) to Daphnia magna ( D. magna ) under different exposure concentrations and temperatures. The results show that although competitive bioconcentration exists, the combined toxicity of the PFAA mixtures to D. magna is synergistic. These contradictory phenomena occur because although the longer-chain PFDoA inhibits the bioconcentration of the shorter-chain PFOA and PFDA, the bioconcentration of PFDoA itself is promoted, and PFDoA is more toxic to D. magna than PFOA and PFDA. The toxic equivalent concentration for the PFAA mixture is 1.38–1.67 times higher than that obtained from simple addition for the three PFAAs when exposed separately. Moreover, elevated temperature promotes not only the bioconcentration of each PFAA and the competition of bioconcentration between shorter-chain and longer-chain PAFF, but also the synergistic toxicity of PFAA mixtures to D. magna . This study suggests that the effect of the interactions among different PFAAs on their bioconcentration and toxicity under different water environmental conditions, such as temperature, should be considered for ecological risk assessment of PFAA mixtures. Graphical abstract: Image 1 Highlights: The longer-chain PFAA inhibit the bioconcentration of shorter-chain PFAA to D. magna. The combined toxicity of long-chain PFAA mixtures to D. magna is synergistic. Bioconcentration competition among PFAAs leads to increased toxicity of longer-chain PFAA. Elevated temperature promotes the competition between the shorter- and the longer-chain PFAA. Elevated temperature enhances synergistic toxicity of PFAA mixtures to D. magna.